Rheumatologic and autoimmune manifestations in primary immune deficiency. Issue 6 (December 2019) - Kitcharoensakkul, Maleewan; Cooper, Megan A.
Abstract : Purpose of review: Here we review the rheumatologic and autoimmune features of primary immune deficiencies with a focus on recently recognized genetic diseases, the spectrum of autoimmunity in PID, and targeted therapies. Recent findings: Primary immune deficiencies (PIDs) were initially described as genetic diseases of the immune system leading to susceptibility to infection. It is now well recognized that immune dysfunction and dysregulation also cause noninfectious complications including autoimmunity. The increased application of molecular testing for PID has revealed the diversity of clinical disease. Recent discoveries of diseases with prominent autoimmunity include activated phosphoinositide 3-kinase δ syndrome and PIDs caused by gain-of-function in STAT1 and STAT3. Similarly, identification of larger cohorts of patients with molecular diagnoses in more common PIDs, such as common variable immune deficiency (CVID), has led to increased understanding of the range of autoimmunity in PIDs. Understanding the molecular basis of these PIDs has the potential to lead to targeted therapy to treat associated autoimmunity. Summary: Autoimmunity and rheumatologic disease can be presenting symptoms and/or complicating features of primary immunodeficiencies. Evaluation for PIDs in patients who have early-onset, multiple, and/or atypical autoimmunity can enhance diagnosis and therapeutic options.